Eternal Return on Capital: Nihilistic Repetition in the Asset Economy - Amin Samman (City, University of London, City Political Economy Research Centre (CITYPERC), 2020)
What can the idea of eternal return tell us about contemporary financial society? In this essay I follow Nietzsche by deploying it as an existential provocation, linking the prospect of endless recurrence to the daily routines of the asset economy. This entails a departure from simple notions of cyclical time, typically associated with political economy and the study of economic history, in favor of a more complex view that sees recurrence and return as figures that organize and reflect the experience of life under the sign of finance. In particular, I argue that the reordering of class around the axis of asset ownership has produced two seemingly distinct structures of feeling- one based on the thrill of endless turnover and return on capital, the other on the drudgery of recurring payment schedules and debt rollovers. Though on the surface at odds with each other, both are anchored in a deeper libidinal economy associated with the asset form and ultimately nihilistic in character. The asset economy should therefore be seen as producing a very peculiar form of eternity based on the abolition of time through repetition. I conclude by foregrounding questions of culture and imagination, exploring these in connection with contemporary forms of on-demand television and the possibility of a time beyond the bad eternity of the asset economy.
Keywords: 330; Temporality; nihilism; history; historical imagination; finance; economic cycles; asset economy; digital capitalism; eternal return; philosophy of history